Desenvolvimento de tecnologias cívicas sob a perspectiva da capacidade de absorção - Lima, Danilo Angelus Pereira de (2021)
The research had as general objective to analyze the characteristics of the absorptive capacity in the development of civic technologies. The investigation took place through a case study and cross-analysis in two Brazilian startups, chosen for applying civic technology, for being recognized in the community for their social impact; the researcher's accessibility to organizations; and the national scope of its activities. The results indicate that the absorptive capacity, in both organizations, is developed through the acquisition, assimilation, transformation and exploitation dimensions and that, in the context of civic technologies, the absorptive capacity explores particular strategies and determinants, such as community mapping, support from the network of external collaborators, co-production and evaluation of user feedback. The research contributes to the advancement of literature as it deepened the understanding of factors and strategies for the development of civic technology; offered an opportunity to understand how Brazilian local communities are appropriating civic technology, indicating new experiences and strategies; and by examining the dimensions and determinants of absorptive capacity in the unprecedented context of civic technologies, updating and expanding the findings already published on this topic.